Large elastocaloric effect in a Ni–Co–Mn–Sn magnetic shape memory alloy. (15th February 2016) - Yang, Z.; Cong, D.Y.; Huang, L.; Nie, Z.H.; Sun, X.M.; Zhang, Q.H.; Wang, Y.D.
Abstract: Exploration of high-performance elastocaloric materials is of great significance to the development of environmentally friendly mechanocaloric cooling technology that could potentially substitute the conventional cooling technology based on vapor compression. In the present work, the elastocaloric effect of a polycrystalline Ni43.5 Co6.5 Mn39 Sn11 magnetic shape alloy was investigated mainly by mechanical testing. A large stress-induced entropy change of 11.1 J kg − 1 °C − 1 under 310 MPa was achieved, which corresponds to more than 80% of the maximum attainable value, i.e. the transformation entropy change. Incorporating the advantages of low cost, non-toxicity, easy fabrication, and abundance in constituent elements, this alloy shows promising prospects for solid-state elastocaloric refrigeration applications. This study also provides instructive information for the design of high-performance elastocaloric materials. Graphical abstract: Highlights: A large elastocaloric effect was achieved in a Ni-Co-Mn-Sn magnetic shape memory alloy. The stress-induced entropy change reaches 11J/(kg °C) under 310MPa, which is more than 80% of the maximum attainable value.